Lattice dynamics of binary and ternary phases in Ti–Si–C system: A combined Raman spectroscopy and density functional theory study - Wdowik, U.D.; Twardowska, A.; Mȩdala-Wa̧sik, M. (Materials chemistry and physics, 2015)
Results of the x-ray diffraction and the Raman spectroscopy experiments on the multiphase Ti–Si–C system containing Ti3SiC2 as the major phase and TiSi2, TiCx, and Ti5Si3/Ti5Si3Cx impurity phases are reported. Experimental studies are supported by the density functional theory calculations of the Raman spectra performed for the major and concomitant phases. The effect of carbon vacancies and impurities on the TiCx and Ti5Si3Cx Raman spectra is investigated. It is shown that identification and refinement of the phase composition of the multicomponent Ti–Si–C system based on the theoretical Raman spectroscopy can be achieved when both frequencies and intensities of the simulated Raman-active modes are simultaneously considered. •Multiphase Ti-Si-C system is explored by Raman spectroscopy and DFT methods.•Ab initio Raman spectra of Ti3SiC2, TiSi2, TiCx, Ti5Si3/Ti5Si3Cx are investigated.•Raman intensities play key role in refinement of spectra from multiphase samples.